In Vitro Activity of TR-700, the Antibacterial Moiety of the Prodrug TR-701, against Linezolid-Resistant Strains - Shaw, K. J. (American Society for Microbiology (ASM), 2008)
TR-701 is the orally active prodrug of TR-700, a novel oxazolidinone that demonstrates four- to eightfold-greater activity than linezolid (LZD) against Staphylococcus and Enterococcus spp. In this study evaluating the in vitro sensitivity of LZD-resistant isolates, TR-700 demonstrated 8- to 16-fold-greater potency than LZD against all strains tested, including methicillin-resistant Staphylococcus aureus (MRSA), strains of MRSA carrying the mobile cfr methyltransferase gene, and vancomycin-resistant enterococci. The MIC(90) for TR-700 against LZD-resistant S. aureus was 2 μg/ml, demonstrating the utility of TR-700 against LZD-resistant strains. A model of TR-700 binding to 23S rRNA suggests that the increased potency of TR-700 is due to additional target site interactions and that TR-700 binding is less reliant on target residues associated with resistance to LZD.